The Effect of the Parameters of Inclusions on the Effective Properties of Materials in Terms of Micromechanics; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Anisimova M. A. Mariya Aleksandrovna (2015, 2015)
Title screen